As 'Alavancas Meta' no discurso do professor de álgebra linear - Padredi, Zoraide Lúcia do Nascimento (2003)
The purpose of this work is to investigate meta resources suggested by teachers, to contribute to the students better comprehension of the notion of basis of vectorial space. In doing so, six teachers were interviewed. The analysis of the interviews supported by Dorier, Robert, Robinet and Rogalski ideas about meta lever and the Harel s principles for the teaching and learning of Linear Algebra. The conclusion presents different Meta resources that could became meta lever for students better comprehension